The practical theological challenges faced by the Apostolic Faith Mission of South Africa Fountain of Life Congregation in the Winterveldt community - Sejeng, Mankopane Sydney (Stellenbosch : Stellenbosch University, 2011)
Thesis (MTh)--Stellenbosch University, 2011.